2020
DOI: 10.3892/ol.2020.11831
|View full text |Cite
|
Sign up to set email alerts
|

Next generation sequencing‑based analysis of mitochondrial DNA characteristics in plasma extracellular vesicles of patients with hepatocellular carcinoma

Abstract: Emerging evidence has revealed that mitochondrial DNA (mtDNA) is encapsulated in plasma extracellular vesicles (EVs). However, the characteristics of mtDNA in EVs from patients with cancer remain largely unexplored, which greatly limits its clinical application. Whole genome and capture-based sequencing found that EV mtDNA covered the whole mitochondrial genome. The medium fragment size in EV mtDNA was significantly larger compared with that in cell-free mtDNA [cfmtDNA; 159 vs. 109 base pairs (bp); P<0.001]. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 38 publications
1
19
0
2
Order By: Relevance
“…However, LC-WGS is restricted by the use of samples in which the tumor fraction is relatively high (> 10%), thus the search for alternative sources of circulating DNA is critical 33 . A recent study found that EV-DNA contained a higher mitochondrial DNA copy number than that found in cf-DNA of patients with hepatocellular carcinoma using whole genome and capture-based sequencing, suggesting EV-DNA may be an advantageous source of alternative liquid biopsy 34 . Our study is one of the few published studies that has investigated the utility of LC-WGS as a method of CNA profiling using low-input EV-associated DNA from cancer patients’ plasma with comparison to matched FFPE samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, LC-WGS is restricted by the use of samples in which the tumor fraction is relatively high (> 10%), thus the search for alternative sources of circulating DNA is critical 33 . A recent study found that EV-DNA contained a higher mitochondrial DNA copy number than that found in cf-DNA of patients with hepatocellular carcinoma using whole genome and capture-based sequencing, suggesting EV-DNA may be an advantageous source of alternative liquid biopsy 34 . Our study is one of the few published studies that has investigated the utility of LC-WGS as a method of CNA profiling using low-input EV-associated DNA from cancer patients’ plasma with comparison to matched FFPE samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mtDNA copy number gained more and more attention in cancer research. Previous studies showed decreased copy numbers in cancer samples in HCC, bladder cancer, breast cancer, kidney clear cell carcinoma and myeloproliferative neoplasm, and increased copy number detected in chronic lymphocytic leukemia, lung squamous cell carcinoma and pancreatic adenocarcinoma (45)(46)(47)(48)(49)(50). Furthermore, the decrease in mtDNA copy number was more significant in female HCC patients than in males (51).…”
Section: Discussionmentioning
confidence: 81%
“…Low-pass WGS (LP-WGS) studies of ctDNA in breast cancer have determined that CNVs associated with metastatic progression and treatment response can be observed longitudinally throughout patient treatment [ 5 , 6 ]. Recent data have also indicated that cancer-related CNVs can be detected in the DNA of cancer patient-derived extracellular vesicles (EVs), which are membrane-bound vesicles released from a wide range of cells including tumour cells via exocytosis or membrane budding [ 7 , 8 , 9 , 10 , 11 , 12 ]. Interestingly, EVs are thought to be stable in the blood for up to 30 days, and the DNA within them is protected from nuclease degradation by the vesicle lipid membrane, suggesting that the assessment of EV DNA may be a promising alternative or complement to ctDNA for non-invasive cancer diagnosis and monitoring [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%